Nature of Discussions about Systemic Therapy Discontinuation or Hospice among Patients, Families, and Palliative Care Clinicians during Care for Incurable Cancer: A Qualitative Study - Traeger, Lara (J Palliat Med, 2020)
Background: Patient/clinician communication is critical to quality cancer care at the end-of-life (EOL). Yet discussions about systemic therapy discontinuation or hospice as a care option are commonly deferred. Real-time communication about these complex topics has not been evaluated. Palliative care visits may provide useful insight into how communication about EOL care occurs over time. Objective: To explore the nature of discussions about systemic therapy discontinuation and hospice among patients, families, and palliative care clinicians during care for incurable cancer. Design: Qualitative study of palliative care visits. Setting/Subjects: We audiorecorded visits of patients and families who participated in a palliative care trial from diagnosis of incurable lung or noncolorectal gastrointestinal cancer through the course of cancer care (n = 30). Measurements: We used thematic analysis to characterize communication patterns in the context of clinical events. Results: Content and tenor of discussions shifted in relation to patient health status. In the absence of acute medical deterioration, discussions addressed hospice broadly as an EOL care option. Candid exchanges between patients and families and their clinicians supported increasing depth and specificity of EOL care communication. As clinicians identified that patients were not tolerating treatment, the clinicians encouraged contemplation about quality-of-life implications of continuing treatment or the possibility that treatment might harm more than help, in anticipation of change in health status. Conclusions: Longitudinal relationships with palliative care clinicians functioned through multiple pathways to support patients and families in making complex EOL care decisions. Results inform models and interventions of communication at the EOL.